Keep It Simple: A Field Experiment on Information Sharing among Strangers - Catia Batista; Marcel Fafchamps; Pedro C. Vicente (Institute of Labor Economics (IZA), 2021)
SMS information campaigns are increasingly used for policy. We conduct a field experiment to study information sharing through mobile phone messages. Subjects are rural households in Mozambique who have access to mobile money. In the baseline intervention, subjects receive an SMS containing simple instructions on how to redeem a voucher for mobile money. They can share this non-rival information with other exogenously assigned subjects unknown to them. We find that few participants redeem the voucher. They nonetheless share it with others and many share information about the voucher they do not use themselves. Information is shared more when communication is anonymous and we find no evidence of more sharing with subjects who have similar characteristics. We introduce treatments to increase the cost of sending a message, shame those who do not send the voucher to others, or allow subjects to appropriate the value of information. All these treatments decrease information sharing. To encourage information diffusion among strangers, the best is to 'keep it simple'.
Keywords: D83; D64; O33; 330; SMS information campaign; nudging; mobile money; anonymity; empathy; shared identity